Online Social Network Use by Health Care Providers in a High Traffic Patient Care Environment - Black, Erik; Light, Jennifer; Paradise Black, Nicole; Thompson, Lindsay (JMIR Publications, 2013)
BackgroundThe majority of workers, regardless of age or occupational status, report engaging in personal Internet use in the workplace. There is little understanding of the impact that personal Internet use may have on patient care in acute clinical settings. ObjectiveThe objective of this study was to investigate the volume of one form of personal Internet use-online social networking (Facebook)-generated by workstations in the emergency department (ED) in contrast to measures of clinical volume and severity. MethodsThe research team analyzed anonymous network utilization records for 68 workstations located in the emergency medicine department within one academic medical center for 15 consecutive days (12/29/2009 to 1/12/2010). This data was compared to ED work index (EDWIN) data derived by the hospital information systems. ResultsHealth care workers spent an accumulated 4349 minutes (72.5 hours) browsing Facebook, staff cumulatively visited Facebook 9369 times and spent, on average, 12.0 minutes per hour browsing Facebook. There was a statistically significant difference in the time spent on Facebook according to time of day (19.8 minutes per hour versus 4.3 minutes per hour, P<.001). There was a significant, positive correlation between EDWIN scores and time spent on Facebook (r=.266, P<.001). ConclusionsFacebook use constituted a substantive percentage of staff time during the 15-day observation period. Facebook use increased with increased patient volume and severity within the ED.